Hollow Structure and Electron Promotion Effect of Mesoporous Pd/CeO2 Catalyst for Enhanced Catalytic Hydrogenation. Issue 5 (5th January 2018) - Wei, Qinhong; Ma, Qingxiang; Zuo, Pingping; Fan, Huailin; Qu, Shijie; Shen, Wenzhong
Abstract: A hollow structured CeO2 spheres supported metallic Pd catalyst (Pd/CeO2 ‐H) was designed and prepared by a glucose hydrothermal method and impregnation method. The CeO2 ‐H consisted of an inner hollow cavity and an outer shell on which a large number of mesopores were formed. The Pd/CeO2 ‐H hollow sphere catalyst, which presented abundant surface oxygen vacancies, was investigated for catalytic hydrogenations of styrene and nitrobenzene to produce ethylbenzene and aniline. Activity tests indicated that the mesoporous Pd/CeO2 ‐H hollow sphere catalyst exhibited striking catalytic activity, which was attributed to the spatial core–shell structure that provided more active sites and facilitated reactant diffusion as well as surface defects (oxygen vacancies), which were capable of transferring electrons to metallic Pd. All of these advances are beneficial to give a higher catalytic hydrogenation performance. Abstract : Hollow hydrogenation : A hollow CeO2 spheres supported metallic Pd catalyst was prepared by employing a glucose hydrothermal method and impregnation method. The Pd/CeO2 hollow sphere catalyst, which consisted of a hollow cavity and outer shell, presented a higher catalytic hydrogenation performance of styrene and nitrobenzene to produce ethylbenzene and aniline, better than that of the general CeO2 ‐supported Pd catalyst.